HUBUNGAN SUSTAINABILITY PERFORMANCE DAN ACCOUNTING ASSURORS TERHADAP ASSURANCE PROCESS DEPTH DAN ASSURANCE STATEMENT BREADTH - Alifia Octa Putri Hermawan; Aditya Septiani (Diponegoro Journal of Accounting, 2022)
This research aims to analyze and empirically prove the relationship between sustainability performance and accounting assurors on a sustainability assurance engagement. This research can contribute to the research that has been done previously and can be used as additional input and comparison for other upcoming research on a sustainability assurance engagement. The focus of this research was reviewed based on the characteristics of each variable. Sustainability performance was reviewed based on high-quality and low-quality sustainability performance, accounting assurors were reviewed based on accounting assurors KAP and non-KAP, and sustainability assurance engagement was reviewed based on 2 indicators, assurance process depth, and assurance statement breadth.This research uses samples from companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020 which publish sustainability reports and are accompanied by independent assurance statements with a total sample of 48 samples. Sampling was based on a purposive sampling method that followed by certain criteria. Data analyses that were  used are content analysis, descriptive statistics, and the Mann-Whitney U test.The results of this research indicate that there was a negative relationship between sustainability performance and assurance process depth, which means that companies with low-quality of sustainability performance have a higher level of assurance process depth than companies with a high-quality of sustainability performance and there was a negative relationship between accounting assurors and assurance statement breadth, which means that companies that use accounting assurors have a higher level of assurance statement breadth than companies that use non-accounting assurors. Suggestions further research include increasing the selection of the company population outside of companies listed on the Indonesia Stock Exchange (IDX), selecting enough samples from 1 company sector, or if more can be grouped according to each sector to minimize differences in company characteristics between sectors. , and the use of parametric statistical tests as research hypothesis testing.